2017
DOI: 10.11646/zootaxa.4317.3.4
|View full text |Cite
|
Sign up to set email alerts
|

A new classification of the tribe Hygrotini Portevin, 1929 (Coleoptera: Dytiscidae: Hydroporinae)

Abstract: The tribe Hygrotini Portevin, 1929 is currently composed of four genera, Heroceras Guignot, 1950, Herophydrus Sharp, 1880, Hygrotus Stephens, 1828 (with two subgenera, Coelambus Thomson, 1860, and Hygrotus s. str.), and Hyphoporus Sharp, 1880. A recent molecular phylogeny of the tribe with ca. 45% of the 137 described species of Hygrotini, including the type species of all genus-level taxa, revealed extended para- or polyphyly of the current genera and subgenera (Villastrigo et al., Zoologica Scripta, in press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 594 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…To answer these questions we built a molecular phylogeny with almost half of the 137 known species of the tribe, including all genera and recognised main species groups (Nilsson & Hájek, ,b), and compiled data on the ecological tolerances of all described species from the literature and our own observations. In addition, our results demonstrated that two of the four currently recognised genera of Hygrotini and one subgenus are para‐ or polyphyletic, revealing the need of a new classification of the tribe, which will be presented in a separate paper (Villastrigo, Ribera, Manuel, Millán, & Fery, ).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…To answer these questions we built a molecular phylogeny with almost half of the 137 known species of the tribe, including all genera and recognised main species groups (Nilsson & Hájek, ,b), and compiled data on the ecological tolerances of all described species from the literature and our own observations. In addition, our results demonstrated that two of the four currently recognised genera of Hygrotini and one subgenus are para‐ or polyphyletic, revealing the need of a new classification of the tribe, which will be presented in a separate paper (Villastrigo, Ribera, Manuel, Millán, & Fery, ).…”
Section: Introductionmentioning
confidence: 78%
“…Species of Hyphoporus have always been considered to be related to the species of Herophydrus , of which they differ mostly in the male genital shape (e.g., Biström & Nilsson, ; Miller & Bergsten, ). The non‐monophyly of genera Hygrotus and Herophydrus and subgenera Hygrotus and Coelambus requires a revised classification of the tribe, which will be formalised in a separate paper (Villastrigo et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For most of the species we have taxonomic, distribution and biogeographical information available from recent reviews: for Canthyporus hottentottus (Gemminger and Harold, 1868) see Biström and Nilsson (2006); for Hygrotus inquinatus Boheman 1848 see Biström and Nilsson (2002) for the species' distribution and Villastrigo et al (2017Villastrigo et al ( , 2018 for their phylogenetic placement and taxonomy; for Laccophilus lineatus Aubé 1838 and Laccophilus taeniolatus Régimbart 1889 see Biström et al (2015); for Hydrovatus macrocerus Régimbart 1895 and Hydrovatus sobrinus Omer-Cooper 1957 see Biström (1997).…”
Section: Species Samplingmentioning
confidence: 99%